Pendeteksian Fraud: Peran Big Data dan Audit Forensik - Syahputra, Briyan Efflin; Afnan, Akhmad (Jurnal ASET (Akuntansi Riset), 2020)
The increasing number of fraud cases in Indonesia resulted in significant losses incurred by this country. Therefore, finding an effective method to detect fraud is the focus of many parties, especially the government. This research investigates the influence of big data on forensic audit. A part from that, the influence of big data and forensic audits as mediating variable on fraud detection is also examined. This research is quantitative research with survey method by distributing questionnaires. The respondents in this research were 221 auditors who worked at Badan Pemeriksa Keuangan (BPK) and Badan Pengawasan Keuangan dan Pembangunan (BPKP) Republic of Indonesia. The statistical test in this research was the structural equation modelling (SEM) of SmartPLS.Â  The result showed that big data had a significant and positive effect on forensic audit. This research also proved that big data and forensic audits have a significant and positive influence on fraud detection. In addition, forensic audits have been proven to partially mediate the relationship between big data and fraud detection.